Epidemiology of the domestic and repatriation (Covid-19) Infection in Al Najaf province , Iraq - Al-Shaibani, Ahmed H. Al- Shareef (Journal of the Faculty of Medicine Baghdad, 2020)
ABSTRACT Background: Al-Najaf province , Iraq , has experienced an outbreak of coronavirus disease 2019 (Covid-19). Epidemiological and clinical characteristics of (Covid-19) infection have been reported but a detailed clinical course and risk factors for mortality including medical comorbidities and severity of illness at time of presentation , have not been well described. Methods: From February 24 to April 7, 2020, a case series study done on 123 PCR-confirmed cases of (Covid-19) admitted to Al-Hakeem Hospital And Quarantine Center (AHQC), in Al-Najaf Province, Iraq. Demographics, clinical and laboratory data gathered from a local database at (AHQC). SPSS(statistical package for social sciences) used for statistical analysis. Frequency, percentage, mean and standard deviation used as descriptive statistics. Chi square or Yates corrected chi square used as needed.(P value≤0.05) regarded significant. Results: In total of 123 Patients, most infections occur inside Iraq 96(78%) .The cohort included 67 (54.5%) females and 56 (45.5%) males, mean age was 32.58±18.56 years. most infections were mild or asymptomatic (72.3%). The most common symptoms was fever (74.8% ) , followed by cough (66.7%), headache (59.3%), and dyspnoea (28.5%). Most patients 108(87.8%) recovered and four patients (3.3%) died. There is a significant association between medical comorbidities , severity of illness and patients outcome (P value <0.001). Conclusions: The potential risk factors of medical comorbidities and severity of illness could help clinicians to identify patients with poor prognosis at an early stage and provides the rationale for a treatment strategy of infected patients and optimal antiviral interventions in the future.